Witness/victim interviewing: a survey of real-world investigators’ training and practices - Hyman Gregory, Amy (Psychology, crime & law, 2023)
The U.S. National Institute of Justice’s Eyewitness Evidence: A Guide for Law Enforcement makes recommendations regarding best practice witness interviewing techniques. However, relatively little is known about police training in collecting and documenting evidence from witness interviews. One hundred seventy-seven police officers from three U.S. states (CT, FL, and MA) were surveyed about witness interview training and practices, perceptions of question type, and recording/documentation of interviews. Results indicate awareness of the importance of asking open-ended questions, but training is lacking, particularly regarding question types. Many officers reported using techniques consistent with the Cognitive Interview such as rapport-building, avoiding leading questions, and taking additional steps to assist recall. Seventy-four percent reported recording interviews via notes or electronic recording devices, while 16% indicated only doing so for certain cases/situations. Fourteen percent also acknowledged not documenting their questions in notes or reports, focusing solely on witness responses. In terms of post-interview documentation, 78% acknowledged writing reports using information elicited during witness interviews. In terms of testimony, 82% reported frequently testifying about witness interview content at criminal trials. Findings suggest that although U.S. police interviewers have implemented some best practice techniques, there are still some considerable training needs as evidenced by self-reported practices.